The Factors that Influence the Loan Repayments of Credit Union Members and Performance Analysis on Credit Union - Rasyidi, Achyar; Firdaus, Muhammad; Sasongko, Hendro (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2016)
Takera Credit Cooperative has a high level of non-performing loans (NPL) at 6.60 percent with greater emphasis on financial aspects in measuring its performance. The purpose of this study includes: (1) To analyze the factors that influence the loans repayments of the members of Takera Credit Cooperative to decrease NPL below 5 percent, (2) To evaluate the performance of Takera Credit Cooperative based on the Balanced Scorecard approach, (3) To formulate the alternative policy that become priority in improving the management performance of Takera Cooperative Credit. This research paper uses the case study approach on the factors that influence the loans repayments of the members, which is analyzed using logistic regression and descriptive analysis. The performance of Takera Credit Cooperative is analyzed with AHP in weighting scoring criteria on BSC perspective. The results of this study are: (1) Loans is given to the members in the group with a "common bond". To conduct financial literacy and monitoring members whose age are above 30 years with low income, but with high loans ceiling and interests rate. Maximizing profits from lending and investment assets. (2) Encouraging members to meet obligations and utilize products. To provide rewards for active members. To create a database of members, To employ special staff for financial counseling and marketing. (3) Revising the Standard Operational Procedure on management of loans risk. Providing shuttle service for savings and loan installments. (4) To the competence of staff for education, training, and mentoring. To provide access to the staff to the strategic information through the use of management information system technology. To create individual staff performance agreement form and developing remuneration packages.